Differential utilization of poly(rC) binding protein 2 in translation directed by picornavirus IRES elements. - Walter, B L (1999)
The translation of picornavirus genomic RNAs occurs by a cap-independent mechanism that requires the formation of specific ribonucleoprotein complexes involving host cell factors and highly structured regions of picornavirus 5' noncoding regions known as internal ribosome entry sites (IRES). Although a number of cellular proteins have been shown to be involved in picornavirus RNA translation, the precise role of these factors in picornavirus internal ribosome entry is not understood. In this report, we provide evidence for the existence of distinct mechanisms for the internal initiation of translation between type I and type II picornavirus IRES elements. In vitro translation reactions were conducted in HeLa cell cytoplasmic translation extracts that were depleted of the cellular protein, poly(rC) binding protein 2 (PCBP2). Upon depletion of PCBP2, these extracts possessed a significantly diminished capacity to translate reporter RNAs containing the type I IRES elements of poliovirus, coxsackievirus, or human rhinovirus linked to luciferase; however, the addition of recombinant PCBP2 could reconstitute translation. Furthermore, RNA electrophoretic mobility-shift analysis demonstrated specific interactions between PCBP2 and both type I and type II picornavirus IRES elements; however, the translation of reporter RNAs containing the type II IRES elements of encephalomyocarditis virus and foot-and-mouth disease virus was not PCBP2 dependent. These data demonstrate that PCBP2 is essential for the internal initiation of translation on picornavirus type I IRES elements but is dispensable for translation directed by the structurally distinct type II elements.